The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.5812/asjsm.34228
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses and Performance Analysis Difference between Official and Simulated Karate Combat Conditions

Abstract: Purpose: This study aimed to compare physiological responses and timemotion analysis between official and simulated karate combat. Methods:Ten high-level karatekas participated in this study, which included official and simulated karate combat.Results: Karatekas used more upper-limb attack techniques during official combat compared to simulated ones (6±3 vs 3±1; P=0.05, respectively). For official and simulated karate matches, the numbers of high-intensity actions (i.e. offensive and defensive fighting activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 22 publications
1
38
0
5
Order By: Relevance
“…While there are reports within the literature worldwide, to the authors knowledge there is no such type of research with Brazilian athletes to date. Thus, learning the improvement in both skills and techniques of Karate becomes necessary to comprehend the evolution of the technical/tactical performance in this combat sport Collet et al 11 , being real or simulated competitions the best environment to do so 9,18,22 . Therefore, the aim of the present study was to identify the most commonly used tactics and techniques by the winners and losers in the male "up to 65 Kg 1 st KYU" category at the Brazilian Shotokan Karate Championship of 2017.…”
Section: Introductionmentioning
confidence: 99%
“…While there are reports within the literature worldwide, to the authors knowledge there is no such type of research with Brazilian athletes to date. Thus, learning the improvement in both skills and techniques of Karate becomes necessary to comprehend the evolution of the technical/tactical performance in this combat sport Collet et al 11 , being real or simulated competitions the best environment to do so 9,18,22 . Therefore, the aim of the present study was to identify the most commonly used tactics and techniques by the winners and losers in the male "up to 65 Kg 1 st KYU" category at the Brazilian Shotokan Karate Championship of 2017.…”
Section: Introductionmentioning
confidence: 99%
“…During short-lasting karate fight (kumite) total time of effort to total rest ratio express ed in seconds was 10.0s: 11.9s, however, taking into consider only time of the highest intensive actions 1.6s that ratio was consistent lower. Moreover time profile of simulated and official contest were differ, because of lower time of activity during an official match [20]. Interestingly, among male kara kas there were no differences between winners and defeated players [21].…”
Section: Discussionmentioning
confidence: 91%
“…Whilst it has been reported that any type of competition can increase the risk of metabolic decompensation in T1DM patients (Sigal et al 2013, Murillo et al 2010, Macknight et al 2009, Jimenez et al 2007), combat sports may be especially challenging in these patients. Combat sports are quite unpredictable as far as physiological responses are concerned (Chaabène et al 2014, Bridge et al 2009). The physiological response, including secretion of counterregulatory hormones, may depend on whether the combat is official or simulated, and whether the competitor loses or wins (Chaabène et al 2014, Bridge et al 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Combat sports are quite unpredictable as far as physiological responses are concerned (Chaabène et al 2014, Bridge et al 2009). The physiological response, including secretion of counterregulatory hormones, may depend on whether the combat is official or simulated, and whether the competitor loses or wins (Chaabène et al 2014, Bridge et al 2009). This is why T1DM patients practicing combat sports require an individual approach that takes the “sociophysiology of combat” into consideration.…”
Section: Resultsmentioning
confidence: 99%